Improving Early Reading Skills Through Kokami Media for Children with Mild Mental Retardation - Ages Budiman (Socrates: Journal of Education, Philosophy and Psychology, 2024)
This research was motivated by the existence of problems in children with mild mental retardation in grade IV / C at SLB YPAC West Sumatra, who had difficulty reading at the beginning. Children have difficulty arranging letters into syllables where the child is unable to read the KV pattern syllables (consonant-vowels). Based on the above problems, this study aims to prove that kokami media is able to improve the ability to read beginning, namely reading KV patterned syllables for children with mild mental retardation. The design used in this study is the A-B-A design with the single subject reaserch (SSR) method and the target behavior, namely stringing letters into syllables by reading syllables with a KV pattern (consonant-vowel). The results of this study indicate that the kokami media is able to improve the ability to read early on in children with mild mental retardation. In the inter-condition analysis, the number of variables analyzed with the results of the analysis tends to be stability at conditions A1 0%, B + 12.5% ​​and A2 + 100%. The percentage of overlap at baseline conditions (A1) with intervention conditions was 0% and at baseline conditions after intervention (A2) with intervention conditions was 38%. The 100% figure proves that the hypothesis is accepted and the kokami media can improve the ability to read beginning (reading KV patterned syllables).